Oxidative stress in prostate cancer patients: A systematic review of case control studies - Byeongsang Oh; Gemma Figtree; Daniel Costa; Thomas Eade; George Hruby; Stephanie Lim; Aymen Elfiky; Neil Martine; David Rosenthal; Stephen Clarke; Michael Back (Prostate International, 2016)
Background: Prostate cancer (PCa) is the most common cancer in men in Western countries. In-vitro and in-vivo studies suggest that oxidative stress (OS) and antioxidants play a key role in the pathogenesis of chronic diseases including PCa, which is promoted by the production of reactive oxygen species and impaired antioxidant defense mechanisms. This study evaluates the association between OS and men with PCa. Methods: A literature search was carried out on Medline, PubMed, and ScienceDirect databases, as well as manual searches from inception up to August 2015 using the keywords “Oxidative stress” or “Reactive oxygen species” or “Lipid peroxidation” AND “Prostate cancer.” All studies including data on the measurement of OS biomarkers in PCa were included. Results: Twenty-three case control studies were retrieved with sample sizes ranging from 15 to 3,613 (6,439 participants in total). Markers of OS were significantly higher in patients with PCa compared with control groups in 21 studies. Two self-controlled case studies comparing OS between PCa cells and non-PCa cells in tissue biopsies found OS to be statistically higher in PCa cancer cells. Results on markers of antioxidant capacity (superoxide dismutase, catalase, glutathione, glutathione reductase, glutathione peroxidase, uric acid, lutein, lycopene, beta carotein, vitamin A, vitamin C, vitamin E, and total antioxidants) were not completely consistent in their association with PCa. Conclusions: Upregulated OS profiles and impairment of antioxidant defense systems may play a role in men with PCa. To confirm these findings, robust clinical trials utilizing a personalized approach which monitors both OS and antioxidant markers during therapy are warranted.